MECHANISMS OF FORMING A SYSTEM FOR ORGANIZATION OF LEISURE OF YOUTH OF MODERN UZBEKISTAN - Sabirdjanovna, Abdikadirova Nigora (International Journal of Psychosocial Rehabilitation, 2020)
The long-term socio-economic policy of the Government of Uzbekistan is formed based on the self-realization of each citizen, which can lead to a reduction in social inequality, an increase in the standard of living of the population, the preservation of the independence and cultural values of Uzbekistan, and the strengthening of the country's economic and political role in the world community. These priorities of reforming social policy in modern conditions lead to the need to improve the goals, objectives and social mechanisms of state youth policy at all levels, coordinate the actions of regional legislative and executive authorities, public associations, commercial and non-profit organizations to solve youth problems. One of the most important aspects in this direction is the organization of leisure for modern youth. This article is written with the aim of studying the mechanisms of formation of a youth leisure organization system. The following tasks are defined as: to study the theoretical and methodological foundations of a sociological analysis of youth leisure; identify the main factors and conditions for organizing leisure activities for youth; analyze the specifics of leisure activities of youth; to study the social mechanism of organizing leisure activities of youth in Uzbekistan by regional authorities; to consider the participation of youth in the power regulation of leisure activities.